2015
DOI: 10.1094/phyto-02-15-0049-r
|View full text |Cite
|
Sign up to set email alerts
|

Eighteen New Candidate Effectors of the Phytonematode Heterodera glycines Produced Specifically in the Secretory Esophageal Gland Cells During Parasitism

Abstract: Heterodera glycines, the soybean cyst nematode, is the number one pathogen of soybean (Glycine max). This nematode infects soybean roots and forms an elaborate feeding site in the vascular cylinder. H. glycines produces an arsenal of effector proteins in the secretory esophageal gland cells. More than 60 H. glycines candidate effectors were identified in previous gland-cell-mining projects. However, it is likely that additional candidate effectors remained unidentified. With the goal of identifying remaining H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
107
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(108 citation statements)
references
References 70 publications
1
107
0
Order By: Relevance
“…A). The dorsal gland localization of GLAND4 is consistent with previous findings in H. glycines (Noon etal ., ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…A). The dorsal gland localization of GLAND4 is consistent with previous findings in H. glycines (Noon etal ., ).…”
Section: Resultsmentioning
confidence: 97%
“…GLAND4 is one of many pioneer effectors produced by cyst nematodes that lack significant global alignment to known proteins, and, as such, protein structure and function prediction tools cannot provide reliable insights into the function of GLAND4 (Gao etal ., , Noon etal ., ; Wang etal ., ). Local alignment of GLAND4 to a histone‐like repeat region alongside the confirmation of nuclear localization, performed as part of this study, provided a reason to test the hypothesis that GLAND4 functions as a DNA‐binding protein.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this idea, protease-like effectors have been identified in M. incognita (Neveu et al, 2003;Danchin et al, 2013), G. pallida (Jones et al, 2009), H. glycines (Noon et al, 2015), and Meloidogyne chitwoodi (Roze et al, 2008). Phytonematodes not only secrete protease-like effectors but also target host proteases.…”
Section: Proteolysismentioning
confidence: 83%
“…It has been generally found that, in geographic regions that SCN-resistant cultivars have been grown the longest, field isolates increase in their likelihood in overcoming resistance in cultivars (Faghihi et al, 2010). More recently, effector candidates have been identified from SCN (Noon et al, 2015), but their roles in parasitism remain to be discovered. More recently, effector candidates have been identified from SCN (Noon et al, 2015), but their roles in parasitism remain to be discovered.…”
Section: Impact Of Soybean Cyst Nematode Resistance On Soybean Yieldmentioning
confidence: 99%